Electromyographic studies in a case of foramen magnum meningioma - Liveson, J. A. (1973)
Atrophy of muscles innervated by the lower cervical cord is a well-known feature in patients with foramen magnum tumours. Electromyographic evidence of denervation in the atrophic muscles is presented. The significance and possible mechanisms are reviewed and discussed.